Socialization of a Causalitic Learning Video Model Integrated with Traditional Gendang Beleq Music as an Effort to Strengthen Local Wisdom in Schools - Galuh Elisa Roliana Fatimah (International Journal of Science Education and Science, 2026)
Science learning in junior high schools is often considered difficult and boring due to the memorization-heavy material and complex mathematical formulas, along with a lack of relevance to daily life. To address this, the causalitic learning model, which focuses on qualitative cause-and-effect analysis of natural phenomena, can be applied. Integrating this model with local wisdom, such as traditional Gendang Beleq music, offers a more engaging and contextual learning experience. This community service project aimed to socialize a causalitic learning video integrated with Gendang Beleq to strengthen local wisdom and improve students' understanding at SMPN 3 Labuapi. Survey results showed the video was highly suitable for use, with average scores of 87.8% from students and 96.4% from teachers, both in the "very good" category. The video also supports STEM education by integrating science, technology, engineering, and mathematics concepts within a local cultural context, making it a relevant and engaging approach. Feedback from respondents suggested emphasizing musical instruments in the opening scenes, reducing nature panoramas, and adding variations to enhance learning enthusiasm. Recommendations included showcasing applications and sound meters more frequently as examples, as they were considered interesting and could increase student engagement.